Endothelin-receptor antagonist can reduce blood pressure in patients with hypertension: a meta-analysis. (4th May 2017) - Yuan, Wenming; Cheng, Genyang; Li, Bin; Li, Yansheng; Lu, Shan; Liu, Dong; Xiao, Jing; Zhao, Zhanzheng
Abstract: The aim of this meta-analysis was to assess the effectiveness and safety of endothelin-receptor antagonist (ERA) in the patients with hypertension. Searches of the PubMed, EMBASE, and CENTRAL databases were conducted to include all the randomized control trials (RCTs). Eighteen trials including 4898 patients were used in the meta-analysis, of which nine were classified as low risk of bias and the other nine as unclear risk of bias. There was no statistically significant difference in all-cause mortality between ERA and placebo groups [6 trials, fixed effects model, RR 1.53 (0.89–2.62); random effects model, RR 1.45 (0.84–2.52)]. ERA significantly reduced 24-h ambulatory blood pressure and sitting blood pressure in patients with hypertension [5 trials, 24-h SBP: WMD −7.65 (−8.95 to −6.36), 24-h DBP: WMD −5.92 (−7.50 to −4.33); 18 trials, SBP: WMD −6.12 (−7.87 to −4.36), DBP: WMD −3.81 (−4.82 to −2.80)]. However, ERA had more adverse events [within 24 h: 3 trials, RR 1.16 (0.82–1.65); after 24 h, 13 trials, RR 1.21 (1.08–1.36)] and severe adverse events than placebo controls [SAE: 9 trials, RR 1.34 (1.13–1.60)]. In addition, there is a potential need for further RCTs that focus on the use of ERA in patients with hypertension.